Increasing Beef Cattle Population Through Artificial Insemination Application in Sigi Regency - Marwa, Marwa; Mirajudin, Mirajudin; Abdullah, Sirajuddin (Mitra Sains, 2021)
This research is a descriptive quantitative study aims to know artificial insemination success rates in population increases cattle district of Kinovaru, Biromaru, dan Marawola, Sigi district of Sulawesi Province the middle. The research has been conducted since Maret- December, 2019. The Variables observed are S/C, CR, and CvR these studies use descriptive and regression analysis at a 95% trust level to identify the relationship between the variable of regression equations. The result showed that the average value of S/C was 1.42, value of C/R was 56.7%, dan CvR was 51%. Regression Analysis showed variable affected in increase the population by Artificial Insemination (IB) is Service per Conception (S/C) dan Conception Rate (CR). And didn’t affect variable towards the increasing population of IB is Calving Rate (CvR), with R Square Value 60%.